2023
DOI: 10.1186/s13036-023-00361-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of mesenchymal stem/stromal cells in regenerative medicine and cellular therapy

Abstract: Mesenchymal stem/stromal cells (MSCs) have been carefully examined to have tremendous potential in regenerative medicine. With their immunomodulatory and regenerative properties, MSCs have numerous applications within the clinical sector. MSCs have the properties of multilineage differentiation, paracrine signaling, and can be isolated from various tissues, which makes them a key candidate for applications in numerous organ systems. To accentuate the importance of MSC therapy for a range of clinical indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 146 publications
(166 reference statements)
0
8
0
Order By: Relevance
“…In this study, we incorporated BM-MSCs into ovarian cells to reconstitute the ovarian structure by using phytohemagglutinin. Although previous studies on MSCs have shown surprising results in their ability to promote the regeneration of bone, blood vessels, skin, and peripheral nerves, as well as to improve the symptoms of local ischemia in a variety of organs, including heart, kidneys, and brain, MSCs have been regarded as a "cure-all" in the eld of tissue repair and regenerative medicine [24,34]. Studies also showed that co-cultured of MSCs with follicles could promote follicle survival and development [30,31,35].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we incorporated BM-MSCs into ovarian cells to reconstitute the ovarian structure by using phytohemagglutinin. Although previous studies on MSCs have shown surprising results in their ability to promote the regeneration of bone, blood vessels, skin, and peripheral nerves, as well as to improve the symptoms of local ischemia in a variety of organs, including heart, kidneys, and brain, MSCs have been regarded as a "cure-all" in the eld of tissue repair and regenerative medicine [24,34]. Studies also showed that co-cultured of MSCs with follicles could promote follicle survival and development [30,31,35].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to minimize the immune response for the success of stem cell therapy [ 112 ]. Recent research has shown that the functional advantages of stem cell therapy, to a large extent, were mediated through paracrine functions, and exosomes were the central paracrine functional units [ 113 115 ]. Many studies have confirmed that exosomes secreted by stem cells have protective functions similar to stem cells, making them a promising and effective therapy.…”
Section: Roles Of Exosomes In the Treatment Of Cancer-related Cachexiamentioning
confidence: 99%
“…Full-thickness cutaneous lesions present a global challenge, necessitating innovative solutions for effective treatment, improved patient quality of life, and reduced financial burdens on healthcare systems worldwide . Addressing this challenge, recent studies highlight the outstanding efficacy of mesenchymal stromal cells (MSCs) in skin repair and regeneration . With inherent advantages such as heightened proliferation capacities, reduced susceptibility to immune rejection, and higher regenerative potential, human umbilical cord mesenchymal stromal cells (hucMSCs) have demonstrated superior performance in the field of wound healing. , Increasing research indicates that the regenerative therapeutic efficacy of MSCs is facilitated through the mediation of extracellular vesicles (EVs), which act as crucial components of paracellular secretion.…”
Section: Introductionmentioning
confidence: 99%